Perancangan Ulang Tata Letak Fasilitas Menggunakan Activity Relationship Chart (ARC) di PT. Pos Indonesia (Studi Kasus: Kantor Cabang Pembantu (KCP) Pangkalan 41362) - Darmawan, Rizki; Supriyati, Supriyati; Mukhlisin, Mukhlisin (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The efficiency of facility placement in the workspace is a crucial factor in improving operational performance and service quality. This research was conducted at the Pangkalan Sub Branch Office (KCP) of PT. Pos Indonesia which faced obstacles in form of non oftimal facility layout. In the porpose of doing research using the ARC (Activity Relationship Chart) methods is to analyze and re-evaluate the layout of facilities. The methods used area qualitative in nature and include observation, documentations, interviews. The results of the analysis show that a number of facilities such as data cabinets and equipment cabinets have not been organized according to the degree of proximity, which cuases an increase in movement time and a decrease in work efficiency. Proposed improvements in the form of a new layout design are organized based on activity linkages, with the hope of increasing space efficiency and overall work productivity.